Green Entrepreneurial Intentions and University Support for Green Entrepreneurial Behavior: A Systematic Literature Review - Setiawan, M. Hardi; Amin, Bagas Faliqul; Ratnawati, Intan (LifeSciFi, 2024)
In recent times, there has been a growing concern among businesses about their environmental practices, many businesses continue to operate with the primary goal of maximizing profits while disregarding social benefits. Such businesses do not consider environmental sustainability. The main objective of this research is to explore relevant concepts for green entrepreneurship. Furthermore, for the growth and development of green entrepreneurship, social support from universities is required to identify appropriate behavioral standards. This research uses a systematic literature review. The findings reveal the need for clarification on relevant concepts, such as knowledge transfer in entrepreneurship, green business financing, and green business decision making processes. The study also found that there is a lack of literature on how universities support green entrepreneurship to address traditional entrepreneurial behavior. In other words, there is a lack of information needed to understand the role of universities in promoting the transition to more creative and sustainable green entrepreneurial behavior. Therefore, it is recommended that the research focus more on identifying the processes through which universities support green entrepreneurial behavior. This is expected to contribute to the improvement of green entrepreneurial behavior.